2022
DOI: 10.1007/s11682-022-00714-w
|View full text |Cite
|
Sign up to set email alerts
|

Cortical atrophy is associated with cognitive impairment in Parkinson’s disease: a combined analysis of cortical thickness and functional connectivity

Abstract: We aimed to perform a combined analysis of cortical thickness and functional connectivity to explore their association with cognitive impairment in Parkinson's disease (PD). A total of 53 PD and 15 healthy control subjects were enrolled. PD patients were divided into PD with normal cognition (PD-NC, n = 25), PD with mild cognitive impairment (PD-MCI, n = 11), and PD with dementia (PDD, n = 17). Cognitive status was assessed with the Mini-Mental State Examination (MMSE). Anatomical magnetic resonance imaging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Although the underlying mechanisms and resultant clinical symptoms are complex, the spreading of misfolded α-synuclein in cortices has been confirmed as the main pathophysiological mechanism of neuronal degradation (1,25). Accordingly, previous studies of PD have observed impaired structural networks of cortical atrophy by analyzing cortical thickness or volume (13,26,27). Relative to these findings based on macroscopic architecture, the present study further explored the impaired network topology based on the microstructure of the GM before morphological abnormalities and revealed alterations with aberrant global properties and disrupted nodal centralities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms and resultant clinical symptoms are complex, the spreading of misfolded α-synuclein in cortices has been confirmed as the main pathophysiological mechanism of neuronal degradation (1,25). Accordingly, previous studies of PD have observed impaired structural networks of cortical atrophy by analyzing cortical thickness or volume (13,26,27). Relative to these findings based on macroscopic architecture, the present study further explored the impaired network topology based on the microstructure of the GM before morphological abnormalities and revealed alterations with aberrant global properties and disrupted nodal centralities.…”
Section: Discussionmentioning
confidence: 99%
“…PD-MCI patients showed reduced gray matter volume (GMV) in the temporal and parietal cortex, putamen, amygdala, hippocampus and cerebellum [ 166 ]. Global cognitive dysfunction (mainly non-memory related) was associated with atrophy in the frontal lobe, left middle and inferior temporal gyrus or in the left superior temporal, right fusiform and bilateral lingual regions [ 219 ]. A meta-analysis reported higher GM atrophy in the bilateral prefrontal cortex, left insula and angula gyrus, right supramarginal gyrus and midcingulate cortex in the PD-MCI cohort [ 164 ], while another meta-analysis reported GM atrophy in the left anterior insula, left inferior and orbital frontal gyrus [ 168 ].…”
Section: Neuroimaging Findings In CI In Pd (See Supplement ...mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is one of the most widely used neuroimaging technique that can provide insights into the structural changes occurring in the brain. Several studies have used MRI to investigate the alterations in brain volume, cortical thickness, and white matter integrity that can be linked to cognitive decline in PD ( Beyer et al, 2007 ; Song et al, 2011 ; Mak et al, 2014 ; Gao et al, 2017 ; Devignes et al, 2021 ; Li et al, 2022 ; Zhu et al, 2022 ). For example, PD-MCI patients have shown significant atrophy in the frontotemporal cortices, thalamus, nucleus accumbens, as well as caudate nucleus compared to the PD patients with healthy cognition (PD-HC) ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%